Exploring management development programmes in mncs. Example of eads group - Lisiński, Marek; Szarucki, Marek (Business, Management and Economics Engineering, 2011)
The purpose of this paper is to discover management development programmes in MNCs on the example of the EADS Group. The paper discusses the role of education in management development as well as the goals of managers’ training. The paper provides the latest information regarding the use of various management development methods. Further, it concentrates on the exemplifying of the selected management development programmes at EADS. It also tries to evaluate the perceived efficiency of the programmes based on several opinions of the trainees. Finally, some suggestions for future research are provided.